Metadynamics Simulation Study on the Conformational Transformation of HhaI Methyltransferase: An Induced-Fit Base-Flipping Hypothesis. (19th June 2014) - Jin, Lu; Ye, Fei; Zhao, Dan; Chen, Shijie; Zhu, Kongkai; Zheng, Mingyue; Jiang, Ren-Wang; Jiang, Hualiang; Luo, Cheng
Abstract : DNA methyltransferases play crucial roles in establishing and maintenance of DNA methylation, which is an important epigenetic mark. Flipping the target cytosine out of the DNA helical stack and into the active site of protein provides DNA methyltransferases with an opportunity to access and modify the genetic information hidden in DNA. To investigate the conversion process of base flipping in the HhaI methyltransferase (M.HhaI), we performed different molecular simulation approaches on M.HhaI-DNA-S-adenosylhomocysteine ternary complex. The results demonstrate that the nonspecific binding of DNA to M.HhaI is initially induced by electrostatic interactions. Differences in chemical environment between the major and minor grooves determine the orientation of DNA. Gln237 at the target recognition loop recognizes the GCGC base pair from the major groove side by hydrogen bonds. In addition, catalytic loop motion is a key factor during this process. Our study indicates that base flipping is likely to be an "induced-fit" process. This study provides a solid foundation for future studies on the discovery and development of mechanism-based DNA methyltransferases regulators.